Suporte agrícola a partir de dados da Organizaç\~ao Para a Cooperaç\~ao e o Desenvolvimento Econômico (OCDE): Duas décadas sob análise - Rogério Edivaldo Freitas (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Agricultural support is one of the main tools used by governments to achieve their domestic goals, especially since the food shortages during and immediately after World War II. However, specific agricultural support programs can affect agricultural production in various ways, and support programs can alter the allocation of natural resources domestically and abroad. In this study, we measured agricultural support in OECD-reported countries during the period 2000-2019 using Spearman's correlation coefficient, time trend analysis and clustering procedures. Data from Organization for Economic Co-operation and Development (OECD) from 2000 to 2019 were employed, specifically the Producer Support Estimate (PSE) and Consumer Support Estimate (CSE). We compared the results of two agglomerative clustering methods and identified groups of similar countries on the basis of their consumer support and producer support estimates behavior during the period studied. Some countries, such as Switzerland, South Korea, Turkey and Canada, displayed specific support behavior, while other groups of countries shared similarities such as China, Indonesia and the Philippines; the European Union, Japan and Norway; and Brazil, South Africa and Chile. Policies implications are discussed and further research is recommended, including analyses of top-down geographical unities, crop-specific programs, and the effects of the covid-19 pandemic on agricultural support worldwide, as more data becomes available.
Keywords: Q10; Q18; 330; agricultural support; OECD-reported countries; Spearman's correlation coefficient; clustering